Sensor response formula for sensor based on ZnO nanostructures - Niyom Hongsith (2018)
In this paper, we propose a new and general formula to describe ethanol adsorption mechanism underlying the response enhancement of ZnO nanostructure sensors. The derivation of sensor response formula based on basic chemical reaction at the sensor surface is presented. The formula can be used to explain response enhancement due to effect of metal doping, surface-to-volume ratio, and surface depletion layer. Thus, it can be regarded as a general formula to describe the sensor response characteristics of ZnO sensors. This general formula is a powerful tool for designing ZnO sensor at any desired sensor response. Furthermore, it is reasonable to expand this formula to explain other sensing materials and also to explain for different active gases. © 2009 Elsevier B.V. All rights reserved.